Internet in the classroom - Stanley, Cal; Educational Video Network ([Huntsville, TX] : Educational Video Network)
Examines the ways that the Internet is changing the face of education
Copy available in DVD format
Executive producer, George Russell ; executive editor, Anne Russell
Keywords: Internet in education; Information superhighway in education; Education -- Computer network resources